Students and Teachers Benefit from Mindfulness-Based Stress Reduction in a School-Embedded Pilot Study - Gouda, Sarah; Luong, Minh T.; Schmidt, Stefan; Bauer, Joachim (Frontiers in Psychology, 2016)
Objective: There is a research gap in studies that evaluate the effectiveness of a school-embedded mindfulness-based intervention for both students and teachers. To address this gap, the present pilot study reviews relevant literature and investigates whether students and teachers who participate in separate Mindfulness-Based Stress Reduction (MBSR) courses show improvements across a variety of psychological variables including areas of mental health and creativity. Methods: The study applied a controlled waitlist design with three measurement points. A total of 29 students (n = 15 in the intervention and n = 14 in the waitlist group) and 29 teachers (n = 14 in the intervention and n = 15 in the waitlist group) completed questionnaires before and after the MBSR course. The intervention group was also assessed after a four-month follow-up period. Results: Relative to the control group, significant improvements in self-reported stress, self-regulation, school-specific self-efficacy and interpersonal problems were found among the students who participated in the MBSR course (p < .05, Cohens` d ranges from 0.62-0.68). Medium effect sizes on mindfulness, anxiety and creativity indicate a realistic potential in those areas. By contrast, teachers in the intervention group showed significantly higher self-reported mindfulness levels and reduced interpersonal problems compared to the control group(p < .05, Cohens` d = 0.66 and 0.42, respectively), with medium effect sizes on anxiety and emotion regulation. Conclusion: The present findings contribute to a growing body of studies investigating mindfulness in schools by discussing the similarities and differences in the effects of MBSR on students and teachers as well as stressing the importance of investigating interpersonal effects.